Pengaruh Suasana Cafe, Lokasi, dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Chill Cafe Tumpang (Studi Kasus Pada Pelanggan Chill Cafe Tumpang) - Fitri Dhea Sari; Muhammad Ridwan Basalamah; Tri Sugiarti Ramadhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract In the present research, Cafe Tumpang on JL. Western Hero No. 360, Kebonsari, Tumpang District, Malang Regency is used as a case study to look at how the environment, location, and service quality of cafes effect customer satisfaction. This study's quantitative methodology aims to explain the results of each variable and their correlations with one another. The primary data source was the Likert-scaled survey responses from Chill customers at Cafe Tumpang. The sample computation for this study made use of the slovin formula and a meaningful sample size. The samples included 90 respondents. The results of the study show that location, service level, and cafe environment are all elements that affect customers' pleasure. Part of a cafe environment. Geographical location and level of service have an impact on customer happiness. Keywords: Cafe Atmosphere, Location, Service Quality, and Customer Satisfaction